A DEPTH INSPECTION ON INFORMAL SCHOOL STUDENTS’ DILEMMA IN TRANSLATING ENGLISH ARGUMENTATIVE TEXT TO INDONESIA - St Ayu Surayya; Maini Maini (Universitas Teknokrat Indonesia, 2023)
The aim of this research is to analyse students' difficulties in translating argumentative text. It was conducted at FLC Course. The participant of this research consisted 15 students. The method of this research was descriptive qualitative. The instruments of this research were translation text and questionnaire sheet. The result of this study from translation text, students made mistake which were the ambiguity, sentence pattern, missing words, and non-linguistics factor. In questionnaire sheet, the highest score of students' difficulties was in linguistics factor which was about 55 score. It was difficulty in translating words which had double meaning. In non-linguistics factor, the highest score was 52 score. It was difficulty in translating words that related with ideology value. Besides, there are internal and external factors from within students that affect their difficulties where the internal factor is the students' motivation and interested in learning is lacking. While external factors are a lack of attention from the teacher and parent, inexact of methodologies in leaning and the lack of student facilities in learning. Based on the result above, it can be concluded that students' difficulties in translating argumentative text more dominant come from linguistics factor than non-linguistics factor.